RELIGIOUS AND CULTURAL INFLUENCES VERSUS HEALTHCARE ACCESSIBILITY IN HPV VACCINE UPTAKE AMONG MIDDLE EASTERN WOMEN (The Research of Medical Science Review, 2025)
Aim: To evaluate socio-cultural and economic barriers to HPV vaccination uptake among women in the Middle East. Study Design and Period: A comparative analytical study at the Department of Maternity, Farwaniya Hospital, Ministry of Health, Kuwait, over one year period from December 2023 to December 2024. Study Design: A cross-sectional survey was conducted among women visiting the maternity department to assess knowledge of HPV, perceived risk, and willingness to pay for the vaccine. Methods: Participants reported their demographic information, knowledge about HPV, awareness of HPV-related cancers, and beliefs about vaccination cost. All statistical analyses were performed using chi-square tests, logistic regression, and Mann-Whitney U tests to assess associations and differences between groups across demographics, medical history, and a few other relevant variables. Results: The age group (p < 0.001) showed a significant difference in knowledge about HPV and willingness to pay for the vaccine using statistical analyses. The higher the education level the highest the chance of believing in vaccine effectiveness (OR = 2.5, CI: 1.8-3.4), whereas statistically significant correlations were found between marital status and family support for vaccination (p = 0.003). Correlations showed that greater knowledge about HPV was linked to greater perceived risk of infection (r = 0.45, p < 0.001). Conclusion: The results demonstrate the complex interaction of socio-cultural and economic barriers that impact HPV vaccination among women in the Middle East. Vaccine uptake will continue to be driven by education, and support distance learning opportunities for extended family members, who may also play a role in the decision to vaccinate.